Green abalone, Haliotis fulgens infected with the agent of withering syndrome do not express disease signs under a temperature regime permissive for red abalone, Haliotis rufescens - Moore, James D. (Springer-Verlag, 2009)
All California abalone species have been shown to be susceptible to infection with the bacterial agent of abalone withering syndrome (WS), although expression of signs of the disease may vary between species and with environmental conditions. We examined thermal modulation of WS expression in green abalone Haliotis fulgens at temperatures mimicking El Niño (18.0°C) and La Niña (14.2°C) events in southern California. In contrast to results obtained from previous experiments with red abalone, H. rufescens, the higher temperature did not result in higher infection intensities of the causative agent of the disease nor increase in clinical signs of disease. These results demonstrate clear differences in thermal regulation of disease expression between abalone species, and provide further data suggesting that green abalone should be a target species of recovery efforts in southern California, where WS is endemic.